Tetrahydrocannabinol for neuropsychiatric symptoms in dementia. (9th June 2015) - van den Elsen, Geke A.H.; Ahmed, Amir I.A.; Verkes, Robbert-Jan; Kramers, Cees; Feuth, Ton; Rosenberg, Paul B.; van der Marck, Marjolein A.; Olde Rikkert, Marcel G.M.
<x xml:space="preserve">Abstract</x> Objective: To study the efficacy and safety of low-dose oral tetrahydrocannabinol (THC) in the treatment of dementia-related neuropsychiatric symptoms (NPS). Methods: This is a randomized, double-blind, placebo-controlled study. Patients with dementia and clinically relevant NPS were randomly assigned to receive THC 1.5 mg or matched placebo (1:1) 3 times daily for 3 weeks. Primary outcome was change in Neuropsychiatric Inventory (NPI), assessed at baseline and after 14 and 21 days. Analyses were based on intention-to-treat. Results: Twenty-four patients received THC and 26 received placebo. NPS were reduced during both treatment conditions. The difference in reduction from baseline between THC and placebo was not significant (mean difference NPItotal: 3.2, 95% confidence interval [CI] −3.6 to 10.0), nor were changes in scores for agitation (Cohen-Mansfield Agitation Inventory 4.6, 95% CI −3.0 to 12.2), quality of life (Quality of Life–Alzheimer's Disease −0.5, 95% CI −2.6 to 1.6), or activities of daily living (Barthel Index 0.6, 95% CI −0.8 to 1.9). The number of patients experiencing mild or moderate adverse events was similar (THC, n = 16; placebo, n = 14, p = 0.36). No effects on vital signs, weight, or episodic memory were observed. Conclusions: Oral THC of 4.5 mg daily showed no benefit in NPS, but was well-tolerated, which adds valuable knowledge to the scarce evidence on THC in dementia. The benign adverse event profile of this dosage allows study of whether higher doses are efficacious and equally well-tolerated. Classification of evidence: This study provides Class I evidence that for patients with dementia-related NPS, low-dose THC does not significantly reduce NPS at 21 days, though it is well-tolerated.